2011
DOI: 10.1177/0892705711412813
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the nature of nanoclay on physical and mechanical properties of polypropylene/reed flour nanocomposites

Abstract: In this study, the effect of nanoclay on the physical and mechanical properties of nanocomposites was investigated. Composites based on polypropylene, reed fiber, coupling agent (maleated polypropylene, MAPP) and nanoclay were made by melt compounding and then injection molding. The mass ratio of reed fiber to polypropylene was controlled at 60/40 for all blends. The concentration was varied and set to 0, 2 and 4 per hundred compounds (phc) for nanoclay and 0 and 2 phc for MAPP. Results indicated that the tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 10 publications
2
26
0
2
Order By: Relevance
“…A shifting of the diffraction peak to the lower angle of the clay/RH hybrid filler‐filled high‐density PE (HDPE) nanocomposites was also reported by Kord . Similar observations have also been reported by other researchers . Interestingly, the varying amounts of RH in the RH/MMT hybrid filler‐filled nanocomposite films did not affect the interlayer distance of MMT because no remarkable change was observed in the diffraction peak angles.…”
Section: Resultssupporting
confidence: 90%
“…A shifting of the diffraction peak to the lower angle of the clay/RH hybrid filler‐filled high‐density PE (HDPE) nanocomposites was also reported by Kord . Similar observations have also been reported by other researchers . Interestingly, the varying amounts of RH in the RH/MMT hybrid filler‐filled nanocomposite films did not affect the interlayer distance of MMT because no remarkable change was observed in the diffraction peak angles.…”
Section: Resultssupporting
confidence: 90%
“…However, it is * corresponding author; e-mail: nbbektas@pau.edu.tr seen that these properties can be improved with different compatibilizer [8,11]. As can be seen clearly from the literature, tensile strengths and modulus of elasticity values can be increased with the addition of nanoclay to the polymer matrix [8].…”
Section: Introductionmentioning
confidence: 99%
“…These materials which are called polymer nanocomposite, the particles are spread in more homogeneous form because of the nanoscale size of particles in the polymer matrix and better holding can be achieved as the surface area is increased [5,6]. Several studies have been carried out to improve the mechanical and thermal properties of the polymer matrix adding nanoparticles with suitable compatibilizer [5][6][7][8][9]. It has been observed that the Izod impact resistance is reduced by nanosized particle reinforcement to polymeric materials [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the water absorption and thickness swelling is observed by the hybridization of nanoclay with reed flour besides this it also upgraded the tensile properties of the whole system. Researchers also show the effect of coupling agent on mechanical and physical properties of reed flour/PP/nanoclay hybrid composite [119]. In other work, integration of nanoclay to the HDPE/rice husk system greatly enhanced their mechanical properties [15].…”
Section: Nano Filler/natural Fiber Hybrid Compositesmentioning
confidence: 99%